2012
DOI: 10.1007/s10561-012-9325-1
|View full text |Cite
|
Sign up to set email alerts
|

A standardized laboratory and surgical method for in vitro culture isolation and expansion of primary human Tenon’s fibroblasts

Abstract: Good manufacturing practices guidelines require safer and standardized cell substrates especially for those cell therapy products to treat ocular diseases where fibroblasts are used as feeder layers. However, if these are unavailable for stem cells culturing, murine fibroblasts are regularly used, raising critical issues as accidentally transplanting xenogenous graft and adversely affecting stem cell clinical trials. Moreover, human fibroblasts play a significant role in testing novel ophthalmologic drugs. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…41,42 Drugs, cell survival and proliferation The M2 agonist Arecaidine was purchased from SigmaAldrich. The muscarinic antagonists used were: gallamine, (final concentration 10 ¡6 M, Sigma, Cat.…”
Section: Isolation and Expansion Of Human Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Drugs, cell survival and proliferation The M2 agonist Arecaidine was purchased from SigmaAldrich. The muscarinic antagonists used were: gallamine, (final concentration 10 ¡6 M, Sigma, Cat.…”
Section: Isolation and Expansion Of Human Fibroblastsmentioning
confidence: 99%
“…28 Cell growth of T24 cell lines (2000 cells/well) and human dermal fibroblasts 41,42 was quantified using a colorimetric method (CellTiter 96 AQueus One Solution Cell Proliferation Assay, Promega) according to the manufacturer's instructions. 42,43 M2 receptor silencing The human M2 muscarinic receptor (CHRM2) (ID1129) expression was inhibited in T24, 5637 and HT1197 cells using 4 different siRNAs. The Chromo GAPDH siRNA (20 nM/well) were also used as positive control of transfection.…”
Section: Isolation and Expansion Of Human Fibroblastsmentioning
confidence: 99%
“…We suggest to test products from three different companies and to evaluate at least three different lot numbers to identify the best product. In our experience, we have demonstrated that in TFs cultures AS and FBS exhibit comparable proliferative properties (13). In addition, considering that the percentage of AS in the coculture media is extremely low (0.2 %), the replacement with FBS should not compromise the cell-system and it should contain the minimum risk.…”
Section: When Heterologous Cocultures (Tfs and Lscs Derived Frommentioning
confidence: 91%
“…We recently demonstrated that TFs are eligible candidates as GMP-grade replacement in compliance with European directives and standards (13,14). Herein we propose a double scenario where autologous or heterologous TFs can sustain LSC growth in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…ASC cultures were maintained at a cell density 4000 cells/cm 2 and passaged when reached 80-90% of confluence. Cell growth/viability was assessed by Trypan Blue (Siciliano et al, 2015a;De Falco et al, 2013) and measured by the automatic cell counter Countess® (Life Technology, Monza, Italy). The number of doubling cells was calculated as the following ratio: 3.322 log 10 N/N 0 (N is the final number of cells obtained and N 0 is the number of cells plated) (De Falco et al, 2013).…”
Section: Isolation Characterization and Cell Growth Of Subcutaneous mentioning
confidence: 99%